RESPONDING TO THE NEW NORMAL IN THE TEACHING-LEARNING ENVIRONMENT (Proceedings of the International Conference on Education, 2023)
The COVID-19 epidemic has significantly changed the educational scene around the world. The "New Norm" of learning delivery, which brought about many changes, has an impact on educators, students, and administrators everywhere. Particularly in the Philippines, the educational system is believed to be very different from how many Filipino teachers and students previously experienced it. Therefore, a variety of data gathering techniques were used to examine how educators, students, and administrators will react to the paradigm shift in teaching and learning in the academic year 2021–2022.  The data for the research study came from 53 academic members, 1590 students, and 12 administrative officials of the Technological University of the Philippines.  Data shows that the faculty were still able to plan lessons, carry out the actual teaching, and keep track of their students' progress during the height of the worldwide crisis, which is comparable to how they often operated before the epidemic. Likewise, students asserted that their performance of the assignments had above their expectations and even met them. They even reported that despite the learning modality changing from traditional to flexible learning alternatives, they were still able to attend, comply, and get good grades. In addition, administrators were able to respond speedily by retraining and upgrading the faculty to accept the new idea of the teaching and learning process, both for online and in-person modalities. Indeed, with the results, the 21st-century educators and learners surpassed the challenge of the new normal teaching and learning setup.
Keywords: Amid Pandemic; New Normal; Teaching-Learning